Atividade antioxidante de fucoidan modificado pelo método redox com ácido gálico - Melo, Keylla Dayanne Coêlho Marinho de (2022)
Antioxidant compounds decrease the amount of intracellular reactive oxygen species (ROS) and, consequently, reduce the deleterious effects of ROS in osteoblasts. Here, we modified a 21 kDa fucoidan (FucA) with gallic acid (GA) using the redox method, to potentiate its antioxidant/protective capacity on pre-osteoblast-like cells (MC3T3) against oxidative stress. The 20 kDa FucA-GA contains 37 ± 3.0 mg GA per gram of FucA. FucA-GA was the most efficient antioxidant agent in terms of total antioxidant capacity (2.5 times), reducing power (five times), copper chelation (three times), and superoxide radical scavenging (2 times). Exposure of MC3T3 cells to H2O2 increased ROS levels and activated caspase-3 along with caspase-9. In addition, the cell viability decreased approximately 80%. FucA-GA also provided the most effective protection against oxidative damage caused by H2O2. Treatment with FucA-GA (1.0 mg/mL) increased cell viability (~80%) and decreased intracellular ROS (100%) and caspase activation (~80%). In addition, Fuc-GA (0.1 mg/mL) abolished H2O2-induced oxidative stress in zebra fish embryos. Overall, FucA-GA protected MC3T3 cells from oxidative stress and could represent a possible adjuvant for the treatment of bone fragility by counteracting oxidative phenomena.